Syok Anafilaktik akibat Media Kontras Radiologi – Laporan Kasus: Laporan Kasus - Juanda, Reno (PT Kalbe Farma Tbk., 2026)
Introduction: Anaphylaxis is an acute, life-threatening hypersensitivity reaction characterized by rapid onset and multisystem involvement, including the respiratory, cardiovascular, and mucocutaneous systems. Iodinated radiologic contrast media is recognized as one of the triggers of anaphylactic reactions, although the incidence is relatively low. Case: A 51 year-old male who developed anaphylactic shock after undergoing a contrast-enhanced CT scan using iohexol. One hour after the procedure, the patient experienced weakness, dyspnea, generalized rash, decreased consciousness, hypotension, oxygen desaturation, palpebral and facial edema, and cold extremities. The diagnosis was established based on clinical findings and standard diagnostic criteria for anaphylaxis. The patient’s condition improved after administration of intramuscular epinephrine (1:1000) at a dose of 0.5 mg as first-line therapy, followed by intravenous fluids, oxygen,diphenhydramine, nebulized bronchodilators, and dexamethasone. The patient was subsequently admitted to the intensive care unit for monitoring. Discussion: Anaphylaxis is a severe, acute, and potentially fatal allergic reaction resulting from the massive release of mediators from mast cells, leading to multisystem involvement. The diagnosis was established according to established criteria. Prompt management was initiated, and clinical improvement was observed following standard guideline-based therapy. Conclusion: Early recognition and rapid administration of epinephrine are key to the successful management of contrast media-induced anaphylactic shock.